Tecnologia da Informação, Democracia e Socialismo: o encontro do século? - Pereira Júnior, Alfredo [UNESP]; Paixão Júnior, Valdir Gonzalez [UNESP]; Ilário, Enidio; Luiz Alfredo Chinali [UNESP]Monserrat Neto, José (My University, 2014)
Scientific and technological development in the areas of information, computing and communication systems has been interpreted as a form of control and manipulation of citizens by the state and ruling elites. In this essay, we develop the opposite possibility, namely the use of technologies for control of the state, and illegal acts of the elite, by a majority of the population. We envision and propose the formation of a People's Online Official Forum (FOPO), accompanied by meetings of groups of militancy, to form a political mechanism of popular self-organization that would oversee the functions of Executive, substitute decision-making processes currently under the responsibility of the Legislative, and veto irregular appointments at the top of the Judiciary. The operation of this mechanism - a radicalization of the principle of "government of the people, by the people and for the people" - presumably could provide a new pathway for overcoming the capitalist system towards a truly democratic socialism, an economicpolitical system that would eliminate human exploitation, oppression and alienation. This transition, as yet hypothetical, would be possible with the use of information technology by the organized people, through the systematic control of the acquisition and social use of the property, without the abolition of private property lawfully obtained.

O desenvolvimento científico-tecnológico nas áreas de informática e sistemas de comunicação tem sido interpretado como forma de controle e manipulação dos cidadãos pelo Estado e elites dominantes. Neste ensaio desenvolvemos a possibilidade oposta, a saber, o uso das tecnologias para o controle do Estado, e de atos ilícitos da elite, pela maioria da população. Vislumbramos e propomos a formação de um Fórum Oficial Popular Online (FOPO), acompanhado de encontros presenciais de grupos de militância, de modo a constituir um mecanismo político de auto-organização popular, que teria a função de fiscalizar atos do Executivo, substituir processos decisórios atualmente sob responsabilidade do Legislativo, e vetar nomeações irregulares no topo do Judiciário. A operação deste mecanismo – uma radicalização do “governo do povo, pelo povo e para o povo” – poderia presumivelmente oferecer uma nova via para a superação do regime capitalista rumo a um socialismo verdadeiramente democrático, um regime econômico-político em que seriam minimizadas a exploração, opressão e alienação humanas. Esta transição, por ora hipotética, seria possível com o uso da tecnologia da informação pelo povo organizado, por meio do controle sistemático da aquisição e uso social da propriedade, sem a abolição da propriedade privada obtida de modo lícito.
Technology, democracy and socialism: the meeting of the century?
Keywords: Technology; Information; Democracy; Socialism; Internet; Popular forum; Self-Organization; Informática; Democracia; Socialismo; Internet; Fórum popular; AutoOrganização